2022
DOI: 10.1186/s13048-022-01042-9
|View full text |Cite
|
Sign up to set email alerts
|

The presence of ovarian endometrioma adversely affect ovarian reserve and response to stimulation but not oocyte quality or IVF/ICSI outcomes: a retrospective cohort study

Abstract: Background The possible impact of ovarian endometriomas (OMAs) on in vitro fertilization (IVF) outcomes remains controversial. Therefore, this study aimed to assess the impact of OMAs on IVF cycle parameters, including ovarian reserve and response to stimulation, embryo quality and pregnancy outcomes. Methods This retrospective cohort study included 2067 patients undergoing their first IVF/ICSI cycles between January 2018 and December 2020. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…We demonstrated that the FF from infertile women with endometriosis III/IV with endometrioma had the greatest impact on nuclear maturation. A recent retrospective cohort study showed a lower number of quality embryos in the group of women with endometrioma compared to women without endometriosis, although the cumulative live birth rate did not differ between groups ( Zeng et al ., 2022 ). An endometrioma is characterized by an accumulation of iron and its derivatives, making the environment toxic and hostile to folliculogenesis ( Sanchez et al ., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that the FF from infertile women with endometriosis III/IV with endometrioma had the greatest impact on nuclear maturation. A recent retrospective cohort study showed a lower number of quality embryos in the group of women with endometrioma compared to women without endometriosis, although the cumulative live birth rate did not differ between groups ( Zeng et al ., 2022 ). An endometrioma is characterized by an accumulation of iron and its derivatives, making the environment toxic and hostile to folliculogenesis ( Sanchez et al ., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of endometriomas on ovarian response represents a related but independent issue. Several intra-patient comparisons between the two gonads (affected versus unaffected) have been performed to determine if unilateral ovarian endometriomas could affect ovarian response in women on ART cycles who had not previously had ovarian surgery [ 8 , 12 , 30 33 ]. These studies generally suggest that the presence of these cysts does not significantly impact ovarian response.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, serum AMH levels are significantly lower in women with bilateral endometriomas than in those with unilateral endometrioma [21]. A recent retrospective study demonstrated that both serum AMH level (2.47 ng/mL vs. 3.32 ng/mL, p=0.001) and antral follicle count (8.8 vs. 12.3, p=0.001) were significantly lower in women with endometrioma compared to those without this condition [22]. The presence of endometrioma can lead to adverse effects on the surrounding healthy ovarian tissue, including increased oxidative stress and fibrosis, loss of cortex-specific stroma, smooth muscle cell metaplasia, reduced microvessel density, and impaired follicular maturation, and ultimately contributing to a decrease in follicular density.…”
Section: Ovarian Reserve Response To Ovarian Stimulation and Clinical...mentioning
confidence: 99%